PERAN PEMERINTAH KOTA SEMARANG DALAM MENCIPTAKAN TERTIB BANGUNAN MELALUI PEMBERIAN IJIN MENDIRIKAN BANGUNAN (IMB) DI KECAMATAN TEMBALANG - Nurina Zata Dini; Warsito .; Sulistyowati . (Journal of Politic and Government Studies, 2015)
ABSTRACTIONPhysical developments is one manifestation of the demands of the region. In the process of physical development to note is the order of the building.it is intended that the area remain well ordered in accordance with the spatial plan. one of the districts that are interesting to study is Tembalang. development in Tembalang occurs quite rapidly from year to year, indications of violations order development seen many point desentyand construction of building is irregular and breaking the rules. Therefore, the formulation of the problem in this research is how urgent inclusion IMB in construction of building, why still violations of IMB in Tembalang and how to optimize surveillance the violation. The use method in this research is descriptive qualitative. the primary data from interview, observation, and documentationand secondary data from archives, journals, other sources were associated with this research.this research using data analysis techniques with analysis in the form description, data reduction, and conclusion on the symptoms studied.The research shows IMB is important to spatial planning. Licensing of IMB useful as controller development and do not damage the environment.The factor of violation development in Tembalang is lack of public awareness to IMB, lack of socialization, and less rigorous supervision. optimization of supervision still constrained by lack of personnel issues and weakness in enforcing the rule. Advice among others can be given to improve BPPT and DTKP to increase quality of service, give sosialization to other people and overall supervision and obey the rules. So that people obey the rules spatial existing as well as supporting the physical development order.Keyword: Orderly Building, Building Permit